2012
DOI: 10.5194/acpd-12-33083-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dissolved organic carbon (DOC) and select aldehydes in cloud and fog water: the role of the aqueous phase in impacting trace gas budgets

Abstract: Cloud and fog droplets efficiently scavenge and process water-soluble compounds and thus modify the chemical composition of the gas and particle phases. The concentrations of dissolved organic carbon (DOC) in the aqueous phase reach concentrations on the order of ~10 mg C L<sup>&minus;1</sup> which is typically on the same order of magnitude as the sum of inorganic anions. Aldehydes and carboxylic acids typically comprise a large fraction of DOC because of their high solubility. The dissolution… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 83 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Recent examples of field-based radiation fog research include the documentation of fog composition and identification of pollutant sources Błas et al, 2010;Raja et al, 2008), the effect of droplet size on composition and the production of inorganic aerosol mass (Fahey et al, 2005;Moore et al, 2004a;2004b;Reilly et al, 2001), the removal of trace species from the atmosphere Burkard et al, 2003;Collett et al, 2001), scavenging efficiencies , organic nitrogen speciation and processing Zang and Anastasio, 2003a;2003b;McGregor and Anastasio, 2001), organic carbon speciation and processing Ervens et al, 2013;Ehrenhauser et al, 2012;Raja et al, 2009;Collett et al, 2008;Fuzzi et al, 2002), and secondary particle formation (Kaul et al, 2011;Dall'Osto et al, 2009). Nearly all radiation fog field campaigns are short term, intensive studies with samples obtained during a limited number of events.…”
Section: Introductionmentioning
confidence: 99%
“…Recent examples of field-based radiation fog research include the documentation of fog composition and identification of pollutant sources Błas et al, 2010;Raja et al, 2008), the effect of droplet size on composition and the production of inorganic aerosol mass (Fahey et al, 2005;Moore et al, 2004a;2004b;Reilly et al, 2001), the removal of trace species from the atmosphere Burkard et al, 2003;Collett et al, 2001), scavenging efficiencies , organic nitrogen speciation and processing Zang and Anastasio, 2003a;2003b;McGregor and Anastasio, 2001), organic carbon speciation and processing Ervens et al, 2013;Ehrenhauser et al, 2012;Raja et al, 2009;Collett et al, 2008;Fuzzi et al, 2002), and secondary particle formation (Kaul et al, 2011;Dall'Osto et al, 2009). Nearly all radiation fog field campaigns are short term, intensive studies with samples obtained during a limited number of events.…”
Section: Introductionmentioning
confidence: 99%
“…The Caltech design (initially developed at the California Institute of Technology) includes a fog water collection unit with a mesh or strings, and a fan unit which moves the air through the collection unit. This design has been used since the 1990s (Collett, Oberholzer and Staehelin, 1993;Demoz, Collett and Daube, 1996), with some slight design modifications, such as samplers for organic materials that are made of stainless steel (Collett et al, 2002;2008;Herckes, Leenheer and Collett, 2007;Ervens et al, 2013;Kim et al, 2019), and others for inorganic materials made of PEEK and Teflon (Degefie et al, 2015;Simon et al, 2016;Nieberding et al, 2018). Some even include multi-stage designs for droplet size resolved sampling (Moore et al, 2002;Straub and Collett, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…20,21 The organic-rich phase of atmospheric aerosols can be classified as a liquid ( < 10 2 Pa·s; where is the dynamic viscosity), a semi-solid (10 2 Pa·s < <10 12 Pa·s) or a solid ( > 10 12 Pa·s), depending on ambient conditions and chemical composition. [22][23][24][25] Indeed, Virtanen et al showed that secondary organic aerosol (SOA) could exist in a glassy phase, while other studies suggest that aerosol particles could be characterised as gels or rubbers.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Hygroscopicity is an important property of aerosols, impacting on aerosol particle size and composition, influencing aerosol phase chemical reactions, and affecting optical properties. 11,12 Many thermodynamic models have been developed to estimate the equilibrium partitioning of water and semi-volatile organic components between the gas and condensed phases in atmospheric aerosols. [13][14][15][16][17][18] However, an assumption that thermodynamic equilibrium is always achieved may not be correct when predicting the properties of viscous or amorphous aerosols due to slow mass transport rates arising from slow bulk-phase diffusion.…”
Section: Introductionmentioning
confidence: 99%